RENEWABLE ENERGY INDUSTRY IN THE EU AS A KEY CLIMATE CHANGE DRIVER - PAUL CALANTER (Global Economic Observer, 2025)
The European Union aims to increase the share of energy from renewable sources (RES), mainly to combat climate change, but also to maintain its leading position in high-performance technologies. As a member of the European Union, Romania attaches great importance to the development of this type of energy, as can be easily observed from the ambitious targets set and the massive investments made in this field. This article aims to analyse recent developments in the renewable energy sector in the European Union and in Romania in particular. In the first part of the paper, we conducted a quantitative analysis that included four indicators on renewable energy, and in the second part, we focused on the future development prospects of this sector in Romania. Our main findings show that even though Romania is well positioned in terms of the indicators analysed, the potential of RES is not yet fully exploited. To this extent, measures such as improving support schemes for RES, building and putting into operation new RES electricity generation capacities, in particular wind and solar, modernising existing cogeneration plants, or expanding nuclear generation capacities should be considered.